A New Paradigm Shift in Antithrombotic Therapy - Anita ePudusseri; Raji eShameem; Alex eSpyropoulos (Frontiers Media S.A., 2013)
Decades after the introduction of oral anti-coagulants namely the vitamin K antagonist Warfarin and antiplatelet agents such as Aspirin and Plavix, new classes of direct, small molecule, novel oral anti-coagulant medications and antiplatelet P2Y12 receptor inhibitors have recently become available. For the novel oral anticoagulants, these agents can be separated by direct thrombin inhibitors such as Dabigatran and direct Factor Xa inhibitors such as Rivaroxaban and Apixaban. For next generation antiplatelet agents such as Ticagrelor and Prasugrel, these new P2Y12 receptor inhibitors form the cornerstone of therapy for patients with acute coronary syndrome or undergoing percutaneous interventions. These novel oral antithrombotics are revolutionizing the field of stroke prevention, atrial fibrillation, the management of venous thromboembolism and treatment of acute coronary syndrome. This article reviews the current research developed in order to identify therapeutic effects and establish net clinical benefits of these new oral antithrombotics.